Enhancement of Heat Transfer using Aluminum Oxide Nanofluid on Smooth and Finned Surfaces with COMSOL Multiphysics Simulation in Turbulent Flow - Majdi, Hasan S.; Alabdly, Hussein A.; Hamad, Muayad F.; Hasan, Basim Obaid; Hathal, Mustafa M. (Al-Nahrain Journal for Engineering Sciences, 2019)
Both surface extension and nanofluid methods were used to enhance the heat transfer in a double pipe heat exchanger under turbulent flow conditions. Aluminum oxide nanoparticles were used with different concentrations(0.6-3 g/l)in hot water to increase the heat transfer rate on smooth tube and circular fins tube for a range of Reynolds number4240-19790. The simulation was also performed to predict the heat transfer coefficient and temperature profile for selected conditions in which COMSOL Multiphysics is used. The experimental results revealed that the heat transfer enhancement by both circular fin and nanofluid exhibited an increasing trend with Reynolds number and nanofluid concentration. The conjoint effect of Al2O3 of 3 g/l concentration and circular fin provided largest heat transfer enhancement of 53% for the highest Re investigated. Simulation results showed reasonable agreement with the experimental values of heat transfer coefficient. The simulation showed that the presence of nanofluid on finned surface influenced the temperature profile indicating the increased heat transfer rate.